Peningkatan Kepuasan Masyarakat terhadap Program Inovasi GEMPITA SERA - Hafid, Rachmi Nurul Hidayat; Renni Yuliati; Afriani; Maria Sonda (Jurnal Sains & Kesehatan, 2026)
Positive innovation in maternal and child health services is essential to reduce maternal and infant mortality rates in Indonesia. One proactive effort initiated by Puskesmas Sudiang Kota Makassar is the movement for Assisting Healthy and Prosperous Mothers, Babies, and Toddlers or Gerakan Pendampingan Ibu, Bayi, Balita Sehat (GEMPITA SERA) to detect high-risk pregnancies early and monitor infants and toddlers with problems. This research aims to assess community satisfaction with the GEMPITA SERA innovation program. This research method is pre-experimental with a one-group pre-posttest design using a satisfaction survey questionnaire that examines tangible, reliability, responsiveness, assurance and empathy aspects. The sampling technique used was purposive sampling with a sample size of 66 respondents and the data analysis technique used the Wilcoxon Signed Rank Test. The research results show that the public is delighted with the GEMPITA SERA team and the results of statistical tests found a p-value of 0.000 < 0.05. It was concluded that there was an increase in the average community satisfaction score with the GEMPITA SERA innovation program. This program focuses not only on improving access to health services but also on strengthening communication between the community and health workers, resulting in faster and more accurate service delivery. With ongoing support, the community feels more secure in obtaining maternal and child health services, which ultimately increases satisfaction and trust in the health system.